Increased fatty acid accumulation following overexpression of glycerol‐3‐phosphate dehydrogenase and suppression of β‐oxidation in oleaginous fungus Mortierella alpina. Issue 5 (5th October 2016) - Yang, Hua; Chen, Haiqin; Hao, Guangfei; Mei, Tiantian; Zhang, Hao; Chen, Wei; Chen, Yong Q.
Abstract : Mortierella alpina is an industrial oleaginous fungus. Although its fatty acid synthesis pathways have been thoroughly examined, the mechanism for fatty acid accumulation is still not fully understood. In this study, we analyzed the effect of glycerol‐3‐phosphate (G3P) supply and β‐oxidation suppression during fatty acid accumulation. The NAD + ‐dependent glycerol‐3‐phosphate dehydrogenase coding gene was cloned from M. alpina ATCC 32222 and overexpressed in this organism. Lipid analysis via GC‐MS revealed that overexpression of G3PD1 resulted in a 50% increase in fatty acid content, whereas G3PD2 exerted a less significant effect and G3PD3 had no effect. Simultaneous supplementation with carnitine O‐acetyltransferase inhibitor, R‐etomoxir, further improved fatty acid accumulation up to 49.4% of dry cell weight. Practical applications: Our results suggest that G3PD1 plays an important role during fatty acid accumulation in M. alpina . Suppression of β‐oxidation can significantly increase fatty acid accumulation. These findings have obvious implications for biotechnological strategies to increase the overall level of oil production. Simultaneously, overexpressing G3PD1 and inhibiting genes involved in fatty acid β‐oxidation may be a step forward to achieving further improvements in fatty acid accumulation in M. alpina . G3PD1, catalyzing G3P to DHAP conversion, plays the most important role during fatty acid accumulation in M. alpina compared to G3PD2 and G3PD3. Abstract : G3PD1, catalyzing G3P to DHAP conversion, plays the most important role during fatty acid accumulation in M. alpina compared to G3PD2 and G3PD3.